2022
DOI: 10.3389/fcvm.2022.952621
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and sex differences in carotid-femoral pulse wave velocity in young individuals and elderly with and without type 2 diabetes

Abstract: The incidence of cardiovascular events is higher in the morning than in the evening and differs between sexes. We tested the hypothesis that aortic stiffness, a compelling cardiovascular risk factor, increases in the morning than in the evening in young, healthy individuals between 18 and 30 years (H18–30) or in older individuals between 50 and 80 years, either healthy (H50–80) or with type 2 diabetes (T2DM50–80). Sex differences were also investigated. Carotid-femoral pulse wave velocity (cf-PWV) recorded via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…Despite the circadian changes in VC and BF in the older groups were found, peak systolic velocity scored similar in the morning compared to the evening, suggesting that changes in BF may be independent of the velocity of ventricular ejection or viscoelastic properties of the arterial wall 20,21 . In support of this notion, we have previously shown that carotid‐femoral pulse wave velocity, an index related to central artery stiffness, is similar at 6 a.m. compared to 9 p.m. in elderly individuals with and without T2DM of similar age to those recruited in the present study 36 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Despite the circadian changes in VC and BF in the older groups were found, peak systolic velocity scored similar in the morning compared to the evening, suggesting that changes in BF may be independent of the velocity of ventricular ejection or viscoelastic properties of the arterial wall 20,21 . In support of this notion, we have previously shown that carotid‐femoral pulse wave velocity, an index related to central artery stiffness, is similar at 6 a.m. compared to 9 p.m. in elderly individuals with and without T2DM of similar age to those recruited in the present study 36 …”
Section: Discussionsupporting
confidence: 84%
“…The change-scores confirm that there are sex differences in vascular regulation at a young age that are independent of different baseline values between men and women, and that these differences are abolished with aging. 36,39 The study of sex differences in vascular and microvascular regulation has led to new insights into cardiovascular medicine and prevention. The documentation of potential causes affecting vascular health in one sex has led to translational research and development of therapeutics to apply to the opposite sex, as well as to different treatments between sexes in targeting cardiovascular diseases.…”
Section: Importance Of the Current Findings In The Context Of Microci...mentioning
confidence: 99%
“…It is increasingly accepted that several genetic variations and biological differences influence cardiovascular risk and the pathogenesis of CVD in women 10,11 . Specific sex differences in physiology and pathophysiology could be related to both endogenous and exogenous reproductive hormones, although contemporary data question the protective role of synthetic estrogens 12 .…”
Section: Traditional Cardiovascular Risk Factors In Women: the Centra...mentioning
confidence: 99%
“…9 Traditional cardiovascular risk factors in women: the central role of obesity It is increasingly accepted that several genetic variations and biological differences influence cardiovascular risk and the pathogenesis of CVD in women. 10,11 Specific sex differences in physiology and pathophysiology could be related to both endogenous and exogenous reproductive hormones, although contemporary data question the protective role of synthetic estrogens. 12 It is controversial whether exogenous oestrogen therapy used for contraception and menopause lowers the CVD burden.…”
mentioning
confidence: 99%
“…Diabetes is an important cause of arterial stiffness, and it is very necessary to pay attention to ePWV of patients with diabetes. Clinical studies have shown that patients with diabetes are more likely to develop arterial stiffness and had a higher cf-PWV than people without diabetes (43)(44)(45). The molecular mechanism of arterial stiffness caused by diabetes has also been widely investigated.…”
Section: Discussionmentioning
confidence: 99%